Naiṇī mātā - Cobra Mum: unearthing and enacting the feelings of nine Himalayan Hindu goddesses - Lange, Gerrit (Religion in contemporary Asia, 2025)
Naiṇī (or Nāginā) is the name of nine Hindu goddesses, who rule over nine villages of Pindar valley in the Indian Himalaya. Seven of these goddesses establish the rule over their territory through a half-year-long journey (yātrā), during which they are carried around, embodied in the shape of a bamboo pole. To start such a journey, a Naiṇī has to be literally "unearthed": a clay pot is taken from under the ground, which means that she is brought up from Nāglok, the underworld of serpent deities. Through their yātrās, the Naiṇīs re-establish their family ties to the women of their respective village who have married into other villages. The explicit goal of the rituals, festivals and processions devoted to the Naiṇīs is to make them happy and to ease their anger about a lack of worship. Thus, the question what a Naiṇī feels is at the core of their religion. This study approaches this evasive topic from two angles: the emotions named when people tell about her and the feelings displayed in ritual interactions with her. The wide array of feelings "unearthed" in this sense shows that asking about nonhuman emotions can contribute to our understanding of religion in general